Investigation of mucosal-associated invariant T (MAIT) cells expressing immune checkpoint receptors (TIGIT and CD226) in early-onset preeclampsia. (September 2020) - Meggyes, Matyas; Nagy, David U.; Szigeti, Brigitta; Csiszar, Beata; Sandor, Barbara; Tamas, Peter; Szereday, Laszlo
Abstract: Objective: During our work, we examined the possible contribution of MAIT cells in the pathogenesis of the clinical phase of early-onset preeclampsia and how this could be influenced by TIGIT and CD226 immune checkpoint molecules. Study Design: 37 pregnant women diagnosed with early-onset preeclampsia and 36 healthy, age-matched control women were involved in this study. Peripheral blood mononuclear cells were isolated by density gradient and frozen. After thawing, cells were stained with monoclonal antibodies to characterize MAIT, MAIT-like, and non-MAIT cells. Flow cytometric analyses were used to measure TIGIT, CD226, intracellular perforin, and granzyme B expression. Results: MAIT (CD3+ CD8+ Vα7.2+ CD161++), MAIT-like (CD3+ CD8+ Vα7.2+ CD161+) and non-MAIT (CD3+ CD8+ Vα7.2+ CD161-) cell population were identified based on their CD161 receptor positivity. MAIT cells markedly differed in proportion, TIGIT expression, granzyme B, and perforin content compared to MAIT-like and non-MAIT cells. A significant difference was determined in TIGIT expression by non-MAIT cells and in CD8/CD226 positive relationship between the preeclamptic and healthy condition. Conclusions: Considering that we did not detect a notable difference between early-onset preeclampsia and healthy pregnancy, we suppose that peripheral MAIT cells expressing TIGIT and CD226 immune checkpoint molecules have a marginal role in the pathogenesis of early-onset preeclampsia.